Determinism and contingencies shaped the evolution of mitochondrial protein import - Rout, Samuel; Oeljeklaus, Silke; Makki, Abhijith; Tachezy, Jan; Warscheid, Bettina; Schneider, André (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Mitochondrial protein import requires outer membrane receptors that evolved independently in different lineages. Here we used quantitative proteomics and in vitro binding assays to investigate the substrate preferences of ATOM46 and ATOM69, the two mitochondrial import receptors of Trypanosoma brucei The results show that ATOM46 prefers presequence-containing, hydrophilic proteins that lack transmembrane domains (TMDs), whereas ATOM69 prefers presequence-lacking, hydrophobic substrates that have TMDs. Thus, the ATOM46/yeast Tom20 and the ATOM69/yeast Tom70 pairs have similar substrate preferences. However, ATOM46 mainly uses electrostatic, and Tom20 hydrophobic, interactions for substrate binding. In vivo replacement of T. brucei ATOM46 by yeast Tom20 did not restore import. However, replacement of ATOM69 by the recently discovered Tom36 receptor of Trichomonas hydrogenosomes, while not allowing for growth, restored import of a large subset of trypanosomal proteins that lack TMDs. Thus, even though ATOM69 and Tom36 share the same domain structure and topology, they have different substrate preferences. The study establishes complementation experiments, combined with quantitative proteomics, as a highly versatile and sensitive method to compare in vivo preferences of protein import receptors. Moreover, it illustrates the role determinism and contingencies played in the evolution of mitochondrial protein import receptors.
Keywords: Protein Binding; Saccharomyces cerevisiae Proteins; mitochondria; Mitochondria; mitochondriální importní komplex; Mitochondrial Precursor Protein Import Complex Proteins; Saccharomyces cerevisiae; Mitochondrial Membrane Transport Proteins; Trichomonas; molekulární evoluce; Evolution, Molecular; mitochondriální proteiny; transportní proteiny mitochondriální membrány; Trypanosoma brucei brucei; Carrier Proteins; Mitochondrial Proteins; vazba proteinů; Animals; receptors; zvířata; Saccharomyces cerevisiae - proteiny; Protein Transport; Protein Precursors; protein import; proteinové prekurzory; transport proteinů; transportní proteiny; mitochondrie; Trypanosoma